2023
DOI: 10.1021/acs.langmuir.3c00118
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping–Trapping versus Extraction Mechanism of Bactericidal Activity of MoS2 Nanosheets against Staphylococcus aureus Bacterial Membrane

Abstract: The promising broad-spectrum antibacterial activity of two-dimensional molybdenum disulfide (2D MoS 2 ) has been widely recognized in the past decade. However, a comprehensive understanding of how the antibacterial pathways opted by the MoS 2 nanosheets varies with change in lipid compositions of different bacterial strains is imperative to harness their full antibacterial potential and remains unexplored thus far. Herein, we present an atomistic molecular dynamics (MD) study to investigate the distinct modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In addition, two-dimensional nanomaterials with a large size have shown antibacterial activity, such as graphene oxide and MoS 2 . The lipid in the cell membrane will be destructively extracted by two-dimensional nanomaterials due to the exceptionally strong dispersion interactions and will ultimately disrupt the integrity of bacterial cells. , In order to avoid such disruption, small graphene nanosheets are used in this work. But research studies have demonstrated that both the insertion of blade-like graphene nanosheets and the destructive extraction of lipid molecules by the presence of the lipophilic graphene have been proposed to cause death of the bacterial cell …”
Section: Resultsmentioning
confidence: 99%
“…In addition, two-dimensional nanomaterials with a large size have shown antibacterial activity, such as graphene oxide and MoS 2 . The lipid in the cell membrane will be destructively extracted by two-dimensional nanomaterials due to the exceptionally strong dispersion interactions and will ultimately disrupt the integrity of bacterial cells. , In order to avoid such disruption, small graphene nanosheets are used in this work. But research studies have demonstrated that both the insertion of blade-like graphene nanosheets and the destructive extraction of lipid molecules by the presence of the lipophilic graphene have been proposed to cause death of the bacterial cell …”
Section: Resultsmentioning
confidence: 99%
“…However, UNM displays a better antibacterial performance than UCNRs and Ni-MOF in the absence of NIR light. This can be traced to the “knife-like edges” of the Ni-MOF nanosheets and the rod-shaped UCNRs, which react strongly with the bacterial membrane by physical cutting or insertion during contact with the bacteria . This leads to disruption of the bacterial structure.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the cytoplasmic membrane of a Gram-negative bacterium, E. coli comprises three major lipids; ∼ 75% phosphatidylethanolamine (PE), ∼ 20% phosphatidylglycerol (PG), and ∼ 5% cardiolipin (CL). Gram-negative bacteria are known for their resistance to antibiotics . The outer and cytoplasmic membranes of such bacteria are an important barrier that protects them from the external environment, including antibiotics and disinfectants. An understanding of the composition, structure, and functions of these membranes can provide insights into the mechanisms of antibiotic and disinfectant actions and help in the development of new drugs to combat bacterial infections. Transportation or permeation of medication molecules through the cell membrane barrier is of fundamental importance from a pharmaceutical standpoint. Antipathogenic or antibacterial solutions or disinfectants make bacterial cell membranes too fluid and permeable, which eventually causes them to break. The primary function of typical disinfectants is to breach the outer membrane of infectious agent in order to kill them . Ethanolic disinfectants are found to be effective in killing many pathogens, including viruses, bacteria, and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…CG models of large biomolecular membranes assist in the reduction of high computational costs with heightened computational speed. One can predict the behavior of lipid membranes under different conditions, such as changes in temperature, pressure or external solute ,, or drug presence using MD simulations. These simulations can be utilized to gain insight on the key interactions between lipids, proteins, and other molecules within the membrane.…”
Section: Introductionmentioning
confidence: 99%